Accuracy of preoperative CT staging of acute colonic diverticulitis using the classification of diverticular disease (CDD) – Is there a beneficial impact of water enema and visceral obesity?. Issue 141 (August 2021) - Rausch, Vanessa Hanna; Weinrich, Julius Matthias; Schön, Gerhard; Sabour, Layal; Özden, Cansu; Kaul, Michael Gerhard; Adam, Gerhard; Bannas, Peter; Henes, Frank Oliver
Highlights: Accuracy of CT in staging acute colonic diverticulitis is improved with increased visceral obesity. Water enema has no benefit on the diagnostic accuracy of CT in acute colonic diverticulitis. CT proves high accuracy in staging acute colonic diverticulitis using a CT-based classification system. Abstract: Purpose: We evaluated the accuracy of preoperative CT in staging colonic diverticulitis (ACD) by using the classification of diverticular disease (CDD) and investigated the diagnostic impact of water enema (WE) and visceral obesity. Methods: In this retrospective study, the radiological and hospital information system was searched for patients who underwent CT for clinically suspected ACD prior to surgery between 2009 and 2019. From the initial population (n = 164), we included 155 patients (94.5 %) (85 women; mean age: 58 ± 13 years) matching the following inclusion criteria: i.) clinically suspected ACD, ii.) i.v. contrast-enhanced CT, iii.) surgery for ACD within 1 week after CT, iv.) histopathological report that proved ACD. The remaining 9 patients (5.5 %) were excluded because histopathological reports were lacking (n = 3) or CT was performed without intravenous contrast agent (n = 6). WE (+ butylscopolamine i.v.) was performed in 93 patients (group A, 60 %). 62 patients (group B, 40 %) had no WE. Visceral-to-subcutaneous fat ratio (V/S) was determined for each patient. Two radiologists blinded for final diagnosis independently staged ACD according to CDD and assessed prevalence and confidence ratings of ACD-related CT-findings: pericolonic fat stranding, covered- and free-perforation, local and generalized peritonitis, abscess. Interobserver-agreement of CT-findings were assessed and effects of WE and V/S ratio on the diagnostic accuracy of CT with surgical and histopathological findings as reference were determined by calculating a logistic regression model. Results: CT-staging showed high accuracy (94 %) and excellent interrater-correlation (ICC 0.96) for staging ACD. WE had no positive impact neither on diagnostic accuracy of staging, nor on confidence ratings of ACD-related CT-findings (all p > 0.5). Confidence ratings were significantly higher in examinations without WE for perforation, peritonitis as well as abscesses (all p < 0.5). Confidence ratings for the assessment of local peritonitis improved significantly with higher V/S (p = 0.049). The increase of V/S significantly correlated with the probability for correct CDD staging of ACD in CT (p = 0.023). Conclusion: Increase of visceral obesity significantly improves accuracy of CT in preoperative staging acute colonic diverticulitis. However, independently of the degree of visceral obesity, water enema has no diagnostic benefit and may therefore be omitted. Overall, CT proves high accuracy in preoperative staging ACD using the classification of diverticular disease. Level of Evidence: Retrospective study, observational study.